Oxidative C–H Sulfonylation of Hydrazones Enabled by Electrochemistry - Yang, Qi-Liang; Lei, Ping-Ping; Hao, Er-Jun; Zhang, Bei-Ning; Zhou, Hong-Hao; Li, Wan-Wan; Guo, Hai-Ming (SynOpen, 2023)
An efficient electrochemical oxidative C(sp2)–H sulfonylation of aldehyde hydrazones is described. A variety of sodium sufinates or sulfinic acids participate effectively in this protocol, which provides facile access to an array of alkyl and aromatic sulfonylated hydrazones with up to 96% yield. Large-scale synthesis and product derivatization show the potential utility of this methodology. Preliminary mechanistic investigations including radical-inhibition, electricity on/off experiments, and cyclic voltammetry support a radical pathway.
Keywords: electrochemical synthesis; radical; sulfonylation; hydrazones; sulfinic acid